Al-Mawardi's Thoughts& Its Relevance to Contemporary Political Systems - Abdul Muien; Sepwana Manda Efaprast; Alysia Arianto; Muhammad Juni H; Kustiawan (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study aims to examine in depth the political thought of Imam al-Mawardi and its relevance to the contemporary political system, particularly in the Indonesian context. Through his main work Al-Ahkam al-Sultaniyyah, al-Mawardi views leadership as a collective obligation of the people (fard kifayah) to safeguard religion (hirasat al-din) and regulate worldly affairs (siyasat al-dunya). This study uses a qualitative approach with the Library Research method that combines primary sources from al-Mawardi's work and secondary sources from modern academic research. The analysis is conducted descriptively and analytically to find the relationship between classical Islamic political values ​​and the Indonesian democratic system. The results of the study show that al-Mawardi's political thought demonstrates suitability with contemporary Indonesian politics in terms of the application of the division of legislative, judicial, and executive powers. The concepts of justice (al-'adl), trust (amanah), and benefit (maslahah) in al-Mawardi's thought align with the values ​​of Pancasila and the 1945 Constitution, especially in realizing a just, ethical, and people-oriented government. The concept of shura can be equated with the principle of deliberative democracy, where deliberation leads to consensus, while ahl al-hall wa al-'aqd resembles a modern legislative body. More concretely, al-Mawardi's thinking provides practical frameworks for addressing Indonesia's pressing political challenges: his strict criteria for leadership selection requiring moral integrity, competence, and accountability offers a normative foundation for anti-corruption reforms and merit-based recruitment in public institutions. His concept of hisbah (public accountability) can strengthen civil society oversight mechanisms and the Corruption Eradication Commission (KPK). Furthermore, al-Mawardi's emphasis on maslahah (public welfare) as the ultimate goal of governance provides ethical guidance for policymaking that prioritizes collective benefits over partisan interests, thereby countering political pragmatism. His principle that a leader who violates trust must be removed resonates with contemporary demands for political accountability and impeachment mechanisms, offering Islamic ethical legitimacy to democratic checks and balances in Indonesia's constitutional framework.